DRIP IRIGATION FOR SUSTAINABLE LIFELIHOOD ON DRY-LAND AGRICULTURE (Finansial Analysis on Changing Wather Management Tecnology at the Dryland Agricultural Production Activities) - Nampa, I Wayan; Kaunang, Salmijati; Surayasa, Made Tusan (SOCA: Jurnal Sosial Ekonomi Pertanian, 2019)
East Nua Tengara have’s 3.216.173 hectars dry land potencial for agricultural. Actualy, the land contribution on agricultural production still minimum. Necessary improve technology for increasing land contribution. water is the main factor in the production process other than land and the dry-land, wates is limited availability in Dry-land. Drip irrigation is one of technology to propuses innovation for strengthen capastity and kontinous production in agriculture. This reseach has ben conducted on 2017 at the UPT Laboratorium Pangan Terpadu/PUI Lahan Kering Kepulauan UNDANA. This reseach analysis of change technology veasibility by financial analysis. The result of reseach show’s is the income per are farm activity folowing drip irrigation technology is Rp. 944,278.24 per are (Rp. 94.427.824,- per hectar). From the finansial analysis show farm activity folowing drip irrigation technology is visible and proper for provit on 12% discount rate. Drip irrigation technology develop opportunities to continouing production, and the other hand convensional production only one seasion on one year.